BIMBINGAN ROHANI KRISTEN SEBAGAI SALAH SATU STRATEGI MELAYANI BAGI WARGA BINAAN KRISTIANI DI LEMBAGA PEMASYARAKATAN KELAS IIA PEMUDA TANGERANG PADA BULAN AGUSTUS 2020 - Dyulius Thomas Bilo; Matheus Mangentang; Lisna Novalia; Nehemia Nome; Roce Marsaulina (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
Every Indonesian citizen is expected to be a good citizen, obedient and not violating laws, religious norms, cultural norms and community norms. However, in reality, not all Indonesian citizens comply with these norms. Many violated and were legally convicted and served time in detention in correctional institutions (Lapas) or prisons and detention centers (Rutan) in Indonesia. Every member of the assisted community in prisons and detention centers from various ethnicities, religions and races must get receive spiritual guidance according to their religion. The same applies to the Class IIA Pemuda Tangerang Prison which is located at LPK No.1 Pemuda Tangerang street, especially for the rehabilitation assisted residents because of drug cases who are Christian and Catholic. In certain activities, Christians and Catholics are sometimes combined and sometimes separated, depending on the interests of the activities and settings of the prison officials. Christian Religious Spiritual Guidance Service which is implemented in August 2020 thanks to the collaboration between prison leaders and the central leadership of the Rise and Shine Ministry Foundation, which mandated the Banten Province branch of the Foundation board to carry out these activities. During August the activities were carried out for four times by different teams. Thus the spiritual guidance of Christianity is one of the strategies to serve Christian assisted members intended to equip the assisted residents to realized, repent and change their character according to God's Word and do not repeat acts that violate the law and are ready to return to the family and society after serving their respective sentences.